A guide for self-help guides: best practice implementation - Shafran, Roz; Egan, Sarah J; de Valle, Madelaine; Davey, Emily; Carlbring, Per; Creswell, Cathy; Wade, Tracey D. (Routledge, 2024)
Guided self-help is an evidence-based intervention used globally. Self-help is a fundamental part of the stepped care model of mental health services that enables the efficient use of limited resources. Despite its importance, there is little information defining the role of the guide and the key competences required. In this context, the guide is defined as the person who facilitates and supports the use self-help materials. This article sets out the role of the guide in guided self-help. It considers practical issues such as the importance of engagement to motivate clients for early change, personalising the intervention, structuring sessions, how best to use routine outcome monitoring and supervision requirements. Key competences are proposed, including generic competences to build the relationship as well as specific competences such as being able to clearly convey the role of the guide to clients. Guides should be prepared for “self-help drift”, a concept akin to therapist drift in more traditional therapies. Knowing how to identify mental health problems, use supervision and manage risk and comorbidity are all key requirements for guides. The paper concludes by calling for increased recognition and value of the role of the guide within mental health services. ProQuest Criminal Justice (Alumni)